THE INTERACTION OF LINGUISTIC AND CULTURAL CONTEXT IN INTERPRETING RHETORICAL QUESTIONS IN ENGLISH AND UZBEK (Web of Teachers: Inderscience Research, 2026)
This study investigates the interaction of linguistic and cultural context in the interpretation of rhetorical questions in English and Uzbek. Rhetorical interrogatives, although structurally similar across languages, function as context-dependent pragmatic devices whose meaning is shaped by discourse environment and cultural norms. The research adopts a qualitative comparative approach based on a corpus of 40 examples drawn from literary and discourse-based sources, including “Dunyoning ishlari” by Utkir Hoshimov. The analysis focuses on four main pragmatic functions: emphasis, evaluation, irony, and emotional expression. The findings reveal that linguistic context plays a crucial role in guiding immediate interpretation, while cultural context significantly influences deeper meaning, particularly in Uzbek, where indirectness and politeness are more prominent. In contrast, English rhetorical questions tend to allow more explicit expression of stance. The study contributes to cross-cultural pragmatics by highlighting the dynamic role of context in meaning construction.